The Use of Indirect Corrective Feedback to Eliminate the Grammatical Errors in Students’ Writing - Nia Pujiawati (Journal of English Language Studies, 2018)
This study aims to determine how the benefits of Indirect Corrective Feedback to improve students' ability in reducing the grammatical errors in their writings. To answer the formulation of this problem, the researcher used a descriptive qualitative design. The study included nine students of English Education Department, batch 2012 as participants. The research data was obtained from the student writings of a descriptive paragraph. The student writings were then analyzed to prove how Indirect Corrective Feedback is used during the study. The results of this study indicate that the number of grammatical errors of all participants decreased after they received the Indirect Corrective Feedback from the lecturer.Keywords: indirect corrective feedback, grammatical errors, writing